Parental Stress and Coping Mechanisms in Rearing Children with Intellectual Disability: A Study Conducted in Kathmandu - Shrestha, Amrita; Adhikari, Rajdevi; Pokhrel, Gopal (Birat Journal of Health Sciences, 2022)
Introduction: The birth of a child with an intellectual disability is the most traumatic event experienced by the parents and their families. The main objective of this study is to identify parental stress and coping in rearing children with intellectual disabilities in Kathmandu valley.Methodology: A descriptive cross-sectional study was conducted among 222 parents (either mothers or fathers) of children with an intellectual disability visiting nine organizations selected through probability proportionate to size sampling.  Data were collected through interview techniques using the Nepali-translated Parental Stress Scale and cope tool developed.Results: Maximum respondents (76.1%) were mothers with an overall mean age of 46.28±12.73 years. The major stress expressed was anxiety-related to a child's future after parents' death (19.8%) and most used coping measure was sharing feelings (44.6%) were expressed as major stress and coping measures used respectively. The overall mean score of parental stress was 64.58±9.22 and parental coping was 106.45±9.72. Maximum respondents have a moderate level of stress (54.5%) followed by severe stress (43.2%) and a moderate level of coping (86.9%) followed by a maximum level of coping (13.1%). There was a significant association of level of stress with relationship to the child, parent’s education, and presence of co-disability in the intellectually disabled child. There was a significant association of level of coping with parents’ education.Conclusion: Maximum respondents had a moderate level of stress and a moderate level of coping mechanisms. Parental stress was high in mothers, illiterate parents, and parents having an intellectually disabled child of 17 years or younger. Parental coping was high among Hindu and literate parents.